An observational study on variations of serum uric acid level in patients of depression and healthy controls and its correlation with hidden bipolarity - Shaswata Mandal; Rudraprasad Acharya; Meghadipa Mandal; Anirban Chakrabarty (Asian Journal of Medical Sciences, 2024)
Background: Bipolar disorder (BD) is one of the most studied psychiatric disorders, this being one of the leading causes of disability in young individuals. In search for its predictive biomarker, serum uric acid (UA) level was seen to have a pathophysiologic role in the genesis of BD through oxidative stress and other mechanism. Aims and Objectives: The aim of the study was to estimate serum UA levels in patients with 1st episode depression, to compare serum UA levels between patients and matched healthy controls and to compare serum UA levels between patients with and without hidden bipolarity and therefore, and to evaluate whether it can be used as a predictor of bipolarity. Materials and Methods: A study was conducted in a tertiary care center in Eastern India for a duration of 3 months with a sample size of 92, comprising 46 cases with major depressive disorder (MDD) and 46 control groups of healthy subjects. Their serum UA levels were estimated. The study population was subjected to a mood disorder questionnaire (MDQ) and Montgomery–Asberg Depression Rating Scale (MADRS) scoring. All these data were tabulated in a master sheet and analyzed using Statistical Packages for the Social Sciences 25 software. Results: The mean age of the study population was 32 years with 46 males and 46 females. The mean UA levels for MDD group was 5.27±1.14 mg/dL and for control group was 4.6±1.2 mg/dL, which was seen to be statistically significant (P=0.001). No statistically significant association was seen between the group with a high likelihood of bipolarity versus a low chance of bipolarity with respect to UA levels. A positive correlation was seen between MDQ scores and UA levels of depressed individuals (using Spearmen’s rho: rs=0.345, P=0.019), but not with their MADRS scores. Conclusion: Serum UA levels are significantly higher in depressed patients as compared to healthy subjects. A non-statistical association was seen between UA levels and their bipolar tendencies, owing to a small sample size of comparable groups. However, a higher MDQ score was associated with high UA levels. A larger study population is needed to conclusively establish the predictive role of UA with respect to BD.